TRACHEAL ENDOSCOPY ON THE DIAGNOSIS OF PULMONARY HEMORRAGHYCAL SUBCLINICAL CASES INDUCED BY EXERCISE IN RACING HORSES - Hon Y., Jean (2008)
This study aimed to determine the percentage of Exercise-Induced Pulmonary Hemorrhage (EIPH) by endoscopic evaluation after racing in Thoroughbred horses. A total of 172 horses between 2 to 8 years old (75 females and 97 males) at Monterrico racetrack in Lima were used. The endoscopic tracheal evaluation was done between 30 and 90 minutes of rest after the race. The animals that had blood in the trachea were considered positive. The results showed that 59.9% of the horses were positive to EIPH, but without significant differences due to sex and type of race track.